(3cJGH GdeKdKGJ GdOQjIs - (3LQeGfhS Hf aQMGJ GdMdHj GdeGQhfjs
(3ChdgG (B:s
(3hHYO ajbhd LHQjd Hf aQMGJ GdQGgH GdMdHi GdeGQhfi ef CNhjg GdQgHGf GddHfGfjjf gPg efXheI Ydi fSb efXheI bWQH jMhi cd HjJ efgG KdGK daXGJ eJabGJ GdCMQa eNJdaGJ GdeYGfi s
(3BNQgG (B:s
(3acdeG aJM HGHg hLOg abGd dg eG CfJ Edi bWQH djd dCf GdbWQH ai GddZI GddU hgPG BNQ eG YKQfG Ydjg ef JdNjU gPg GdefXheI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GddZIs